2011
DOI: 10.1002/acp.1635
|View full text |Cite
|
Sign up to set email alerts
|

Typicality effects on memory for voice: Implications for earwitness testimony

Abstract: The effects of voice typicality on voice recognition were examined. In an incidental task, participants were presented with consonant-vowel-consonant stimuli (with varying vowels) spoken by voices rated as high-typical or low-typical. One week later, they were brought back for a surprise voice recognition test where the target voice was presented along with low-typical and high-typical voice distracters. The results indicated that voice misidentifications occur, with many errors due to confusions of hightypica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 33 publications
(46 reference statements)
3
23
0
1
Order By: Relevance
“…More specifically, we have argued for the existence of dynamic, long-lasting 'mean voice' representations at both voice-acoustic and voice-identity stages of processing. In accordance with recent findings in behavioural studies of voice processing (Papcun et al, 1989;Mullennix et al, 2009, Bruckert et al, 2010 and with those in the face processing domain (Loffler et al, 2005), our demonstrations of neural 'mean voice' representations constitute the first neuroimaging evidence that voice representations are centered around prototypes in long-term memory.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…More specifically, we have argued for the existence of dynamic, long-lasting 'mean voice' representations at both voice-acoustic and voice-identity stages of processing. In accordance with recent findings in behavioural studies of voice processing (Papcun et al, 1989;Mullennix et al, 2009, Bruckert et al, 2010 and with those in the face processing domain (Loffler et al, 2005), our demonstrations of neural 'mean voice' representations constitute the first neuroimaging evidence that voice representations are centered around prototypes in long-term memory.…”
Section: Resultssupporting
confidence: 87%
“…In a study on face-identity processing, reduced haemodynamic responses were found in the fusiform face area for central stimuli only when those were also central in the long-term stored face space of the viewer (referred to as 'mean face' stimuli, Loffler et al, 2005), suggesting that long-term central faces are encoded more sparsely. Based on these results and on behavioural findings that have indicated a prototype-centered representation of voices in long-term memory (Papcun et al, 1989;Mullennix et al, 2009;Bruckert et al, 2010), we can expect a typicality-based neural sharpening mechanism for voices similar to that found for faces.…”
Section: Introductionmentioning
confidence: 58%
“…To us, this discussion fits well with the literature on distinctiveness, and links with the recent work of Brédart (2012b, see also Mullenix, Ross, Smith, Kuykendall, Conard &Barb, 2011;Sorensen, 2012;Zetterholm, Sarwar, Thorvaldsson & Allwood, 2012 for further examples of vocal distinctiveness effects). Within their study, Barsics and Brédart explored the retrieval of episodic and semantic information from distinctive and typical faces and voices.…”
Section: Not All Voices Are Created Equal: Robust Exemplarssupporting
confidence: 86%
“…Earlier studies have indicated that voices may be represented in prototype-centered voice spaces (Andics et al, 2010;Bruckert et al, 2010;Latinus et al, 2009;Mullennix et al, 2009;Papcun et al, 1989) and that the STS (Andics et al, 2010;Belin and Zatorre, 2003;Wong et al, 2004) and IFC (Andics et al, 2010; are core voice processing regions, showing voice selectivity and short-term sensitivity to voice similarity. But these voice-selective regions of the STS and the IFC have not previously been shown to be involved in long-term mean-based voice coding, and indeed there has to date been no other evidence of long-term neural coding of voice prototypes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that mean-based coding can also result from long-term adaptation (Kahn and Aguirre, 2012), a mechanism that is sensitive to stimulus distributions. Recent behavioral (Bruckert et al, 2010;Latinus et al, 2009;Mullennix et al, 2009;Papcun et al, 1989) and neuroimaging studies (Andics et al, 2010) also suggest that there is mean-based coding for voices. In other words, voice representations appear to be centered around prototypes in long-term memory.…”
Section: Introductionmentioning
confidence: 95%